Firefighters' noise exposure: a literature review - Taxini, Carla Linhares [UNESP]; Guida, Heraldo Lorena [UNESP] (Fundação Otorrinolaringologia, 2013)
AIM: To review the literature about the effects of environmental noise on the hearing ability of firefighters. METHOD: The PubMed and Scielo databases were searched and studies from 2002 to 2012 that included the keywords firefighters, noise, and hearing loss were identified. Initially, 24 studies were selected, but only 10 met the inclusion criteria of investigating the effects of occupational noise on firefighters. RESULTS: Only 2 (20%) studies quantified levels of sound pressure and performed audiological tests to identify associations with noise intensity and 3 (30%) questionnaire-based studies reported that these professionals are more susceptible to hearing loss. Four (50%) studies found that noise exposure damages the auditory system in this population. DISCUSSION: These findings indicate that there is a necessity for preventive measures to be adopted by this population since it is considered to be at risk. CONCLUSION: In recent years, there have been few studies of firefighters' exposure to occupational noise, but our findings show the importance of new studies that include proper means of quantifying their exposure to noise in different work environments, in order to identify possible adverse conditions as well as to aid in the diagnosis of hearing loss.
Keywords: Noise; Military personnel; Hearing Loss; Hearing; Noise-Induced